Analysis of ecological quality changes and influencing factors in Xiangjiang River Basin - Zhang, Yuanyuan; Yi, Liwen; Xie, Binggeng; Li, Junhan; Xiao, Jianyong; Xie, Jing; Liu, Zhixing (Scientific reports, 2023)
The Xiangjiang River Basin is an important part of the Yangtze River Basin and an important area in Hunan Province. Thus, taking steps to protect the ecological sustainability of the Xiangjiang River Basin, such as the construction of the protection of ecological security in Hunan Province and the Yangtze River Protection Law, is important for national projects However, research on the ecological quality of the Xiangjiang River Basin is mostly biased toward the evaluation of ecosystem services or an individual ecological index. Furthermore, a long-term evaluation of multiple indicators is lacking. Therefore, based on Google Earth Engine and geographic detectors, the remote sensing ecological index was used to evaluate this area. The year-by-year research on the Xiangjiang River Basin from 2001 to 2020 clarified its past ecological quality change trend, explored the reasons for the ecological quality change, and provided a basis for protecting its ecological quality. The following results are presented. (1) Regarding spatial distribution, areas with poor ecological environments are mainly distributed at the centers of Chang-Zhu-Tan, Hengyang, and various districts and counties. (2) Regarding the time variation, the ecological quality of the Xiangjiang River Basin from 2001 to 2020 showed a slight downward trend, with a downward slope of approximately − 0.0000357143; a rapid increase, with a growth rate of approximately 0.00395; And an overall improvement over 20 years. The areas with declining ecological quality are mainly located in the Chang-Zhu-Tan urban agglomeration, the city center of Hengyang, and the county centers of various county towns. (3) The factor detection results show that human factors play a key role in population density and land use, with average q values of 0.429 and 0.353, respectively. Among natural factors, elevation and slope play a key role, with average q values of 0.230 and 0.351, respectively; hence, Land use directly affect on the ecological quality in a location. These findings will provide important information for managers to formulate ecological restoration measures for the Xiangjiang River.